DISCIPLINED, COMPETENT, AND REWARDED: UNPACKING THE DRIVERS OF EMPLOYEE PERFORMANCE IN ISLAMIC BANKING - Yandra Rivaldo (Postgraduate Management Journal, 2024)
This study investigates the effect of work discipline, competence, and reward on employee performance at a branch office of Bank Syariah Indonesia in Batam. Islamic banking has expanded rapidly in Indonesia, yet the human-resource conditions that sustain employee performance in sharia-compliant branch operations remain under-examined relative to conventional banking. A quantitative associative design was used, with a census of all 37 branch employees as respondents. Data were collected via a structured Likert-scale questionnaire and analyzed with multiple linear regression in SPSS 23, following classical assumption testing. The results indicate that work discipline (t = 7.257; p = .000), competence (t = 3.015; p = .004), and reward (t = 3.581; p = .001) each have a positive and significant partial effect on employee performance, and the three variables jointly explain 84.2 percent of the variance in employee performance (R² = .842; F = 82.611; p = .000). Work discipline is the most dominant predictor (β = .514), followed by reward (β = .249) and competence (β = .241). The findings suggest that consistent rule compliance, competence development, and a well-structured reward system are complementary and largely additive drivers of performance in this Islamic banking branch, with practical implications for human-resource practice in similarly structured sharia financial institutions.